Understanding Relationship: Maximizing the Effects of Science Coaching - Anderson, Ruth; Feldman, Sue; Minstrell, Jim (Education Policy Analysis Archives, 2014)
Abstract There is growing empirical evidence that instructional coaching can help teachers transfer their learning from professional trainings (e.g., new strategies) to classroom practice and that coaching promotes greater collaboration and reflection among teachers. At the same time, however, research on the effectiveness of particular coaching models and the underlying reasons for their effectiveness is only beginning to emerge. Why does coaching “work” when it does? What causes it to break down and to what extent can it be repaired? Our five-year mixed methods study of science instructional coaching in a single school district set out to answer these and other questions. Data from multiple sources (surveys, interviews, classroom observations and coaching logs) confirmed a strong correlation between improvements in teacher practice and the time teacher and coach spend together (at least 10 hours for elementary teachers and 20 for secondary) the focus of their work (narrow as opposed to broad); and most importantly, the quality of their professional relationship. In this paper, we present preliminary findings from a follow-up analysis intended to help explicate how relationships seemed to matter in coaching. We believe the findings from the secondary analysis help to clarify coaching interactions and to specify what contributes to or detracts from their productivity. These findings may not only help to inform decisions related to the design, implementation and ongoing maintenance of coaching programs but also provide fodder for considerations related to the organizational capacity, flexibility and adaptability of the schools and school systems.